2020
DOI: 10.1002/jso.26115
|View full text |Cite
|
Sign up to set email alerts
|

The safety of hepatectomy after transarterial radioembolization: Single institution experience and review of the literature

Abstract: Background and Objectives: The liver is a frequent site of malignancy, both primary and metastatic. The treatment goal of patients with liver cancer may include transarterial radioembolization (TARE). There are limited reports on the safety of hepatectomy following TARE. Our study's purpose is to review patients who have received TARE followed by hepatectomy. Methods: A retrospective study was performed on patients diagnosed with any liver cancer from 2013 to 2019 who underwent TARE followed by hepatectomy. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Secondly, major LLR after RE should be performed by a highly experienced laparoscopic liver surgeon. According to the IWATE score [21], median difficulty of LLRs in this MLLR-RE series was 10 (8-11) and the risk of intra-operative events [23] was 9 (9)(10)(11)(12)(13)(14). This represents an expert level of difficulty and a high/extremely high risk of intra-operative complications.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Secondly, major LLR after RE should be performed by a highly experienced laparoscopic liver surgeon. According to the IWATE score [21], median difficulty of LLRs in this MLLR-RE series was 10 (8-11) and the risk of intra-operative events [23] was 9 (9)(10)(11)(12)(13)(14). This represents an expert level of difficulty and a high/extremely high risk of intra-operative complications.…”
Section: Discussionmentioning
confidence: 78%
“…However, perioperative surgical outcomes after RE were unknown until the multicenter Post-SIR-Spheres Surgery Study (P4S) [12] reported the adequate safety of open resection and transplantation after RE. Various articles have been published afterwards showing the outcomes of liver resection after RE [13,14]. Although laparoscopic liver resections (LLRs) have become increasingly widespread worldwide with an increasing number of reported cases, only a few preliminary results from our own experience of LLR post-RE have been reported [15,16].…”
Section: Introductionmentioning
confidence: 99%